2022
DOI: 10.1186/s13059-022-02656-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration and pan-structurome prediction of climate-associated riboSNitches in Arabidopsis

Abstract: Background Genome-wide association studies (GWAS) aim to correlate phenotypic changes with genotypic variation. Upon transcription, single nucleotide variants (SNVs) may alter mRNA structure, with potential impacts on transcript stability, macromolecular interactions, and translation. However, plant genomes have not been assessed for the presence of these structure-altering polymorphisms or “riboSNitches.” Results We experimentally demonstrate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…Of particular note, we also provide riboSNitch predictions, which indicate the likelihood that a variant alters RNA structure, which is a mechanism for differential post-transcriptional regulation (Halvorsen et al, 2010). As shown by our analyses in Arabidopsis (Ferrero-Serrano et al, 2022), riboSNitches are a fruitful topic for investigation.…”
Section: Resultsmentioning
confidence: 88%
“…Of particular note, we also provide riboSNitch predictions, which indicate the likelihood that a variant alters RNA structure, which is a mechanism for differential post-transcriptional regulation (Halvorsen et al, 2010). As shown by our analyses in Arabidopsis (Ferrero-Serrano et al, 2022), riboSNitches are a fruitful topic for investigation.…”
Section: Resultsmentioning
confidence: 88%
“…Overall, our results show that stable secondary structures -as inferred from low MFEscorrelates positively with siRNA abundance and may be shaped by a trade-off between functional requirements and the potential disruptive effects of self-priming. We hope this work sparks further exploration of the roles of secondary structure in plant genome evolution, including the population genetics of mutations in regions of secondary structure (Ferrero-Serrano et al, 2022), their roles in the stress response (Zhu et al, 2018), and comparative analyses of secondary structure characteristics between species.…”
Section: The Self-priming Trade-offmentioning
confidence: 99%
“…Assmann also presented work highlighting the relationship between structure-altering single-nucleotide polymorphisms (SNPs) (riboSNitches) and climatic factors in Arabidopsis. The ZINC RIBBON 3 (ZR3) transcript is an example of a riboSNitch possessing a G to A SNP that alters its secondary structure (Ferrero-Serrano et al, 2022).…”
Section: Rna Structurementioning
confidence: 99%
“…Assmann also presented work highlighting the relationship between structure‐altering single‐nucleotide polymorphisms (SNPs) (riboSNitches) and climatic factors in Arabidopsis. The ZINC RIBBON 3 ( ZR3 ) transcript is an example of a riboSNitch possessing a G to A SNP that alters its secondary structure (Ferrero‐Serrano et al, 2022). It was found that there was a correlation between the frequency of this SNP for ZR3 and the plants' geographical location away from the coast; plants further inland that experienced a wider range of fluctuating temperatures contained a higher percentage of the G to A variant than those growing near the coast.…”
Section: Introductionmentioning
confidence: 99%